TRANSFORMASI DIGITAL DAN PENGEMBANGAN SDM PERTANIAN: STRATEGI MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Hariadi, Untoro; Putri Perdana (Fakultas Pertanian Universitas Janabadra, 2025)
The Indonesian agricultural sector faces significant challenges in entering the era of digitalization and the Industrial Revolution 4.0. This study aims to examine the strategy for developing human resource (HR) competencies in the agricultural sector to face digital transformation through a comprehensive literature study. The results of the study indicate that the digital and competency gaps are still the main obstacles to sustainable agricultural development. The strategy for developing agricultural HR must include: (1) updating the agricultural education curriculum based on digital technology; (2) strengthening training programs and technology assistance for farmers; (3) developing penta-helix partnerships between stakeholders; (4) creating inclusive digital ecosystem in rural areas; and (5) implementing integrated agricultural HR empowerment policies. Implementation of these strategies requires ongoing commitment from the government, educational institutions, the private sector, and farmer communities to create adaptive and competitive agricultural HR in the digital era.